Human adenovirus type 3 restores pharmacologically inhibited exosomal cargo in lung carcinoma cells - Ipinmoroti, Ayodeji O.; Pandit, Rachana; Crenshaw, Brennetta J.; Sims, Brian; Matthews, Qiana L. (Frontiers in Pharmacology, 2024)
Our investigation into the impact of Human Adenovirus type 3 on restoring exosomal cargo in pharmacologically inhibited lung carcinoma cells aligns seamlessly with the scope and specialty of this journal. This research explores the interplay between viral intervention and pharmacological inhibition of exosomes derived from cells of the upper respiratory tract, shedding light on the potential therapeutic avenues relevant to infectious diseases, specifically concerning the modulation of exosomal cargo within a diseased lung microenvironment. We have previously demonstrated these pharmacological agents to successfully inhibit exosome formation without altering the viability of the cells. Understanding these mechanisms holds promise for innovative pharmacological interventions in infectious diseases, thus justifying its relevance and significance within the journal's domain and perspective.